Effects of temperature and polyethylene plastic packaging on physicochemical changes and antioxidant properties of tomato during storage - Nuraina Zahira Azali,; Haslaniza Hashim,; Arnida Hani Teh, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study determined the effects of different storage temperatures and packaging on the physicochemical changes and antioxidant properties of tomatoes during storage in two tomato species (Lycopersicon esculentum Mill. tomato and Solanum lycopersicum var. Cerasiforme cherry tomato). Samples underwent storage process with different temperatures of 4 °C and room temperature (25 °C); with or without polyethylene plastic packaging. The physicochemical changes studied include weight, color, firmness, and total soluble solids (TSS), while the antioxidant properties studied include lycopene content, ascorbic acid content, total phenolic content (TPC), and free radical scavenging activity (2,2-Diphenyl-1-picrylhydrazyl, DPPH), measured at three-time points (day 1, 8, 15). Based on the two-way ANOVA, both temperature and packaging factors play an important role in the physicochemical changes and antioxidant properties of both tomato species. For tomatoes, the temperature had a significant (p<0.05) effect on all measurements, except for redness value (a*) and ascorbic acid content (p>0.05). While packaging had a significant (p<0.05) effect on all measurements, excluding the ascorbic acid and TPC (p>0.05). For cherry tomatoes, the temperature had a significant (p<0.05) effect on all measurements, not including ascorbic acid content (p>0.05). Whereas packaging had a significant (p<0.05) effect on all measurements, except for TPC (p>0.05). For both samples studied, temperature and packaging factors had significant interactions (p<0.05) on all measurements, except for ascorbic acid and TPC (p>0.05). In conclusion, storage at a low temperature of 4 °C with the packaging was found to be able to maintain the physicochemical and antioxidant properties in both tomato species.